Residence proximity to benzene release sites is associated with increased incidence of non‐Hodgkin lymphoma. Issue 18 (29th July 2013) - Bulka, Catherine; Nastoupil, Loretta J.; McClellan, William; Ambinder, Alexander; Phillips, Adrienne; Ward, Kevin; Bayakly, A. Rana; Switchenko, Jeffrey M.; Waller, Lance; Flowers, Christopher R.
<x xml:space="preserve">Abstract</x> BACKGROUND An increased risk of non‐Hodgkin lymphoma (NHL) has been observed among individuals with occupational exposure to benzene, but the risk among those living near benzene release sites has not been well described. METHODS To investigate the spatial patterns of NHL incidence and the association between NHL incidence and distance to benzene release sites, the authors linked and geocoded data on benzene release sites in Georgia from 1988 to 1998 using the Environmental Protection Agency's (EPA) Toxics Release Inventory (TRI), census tract level population statistics, and NHL incidence from the Georgia Comprehensive Cancer Registry (GCCR) from 1999 to 2008. Standardized incidence ratios were mapped by census tract, and a Poisson regression was performed on NHL and NHL subtype incidence data using the mean distance between the tract centroids and release sites as markers of exposure. Cluster analyses were conducted at the global, local, and focal levels. RESULTS Poisson regression indicated that, for every mile the average distance to benzene release sites increased, there was an expected 0.31% decrease in the risk of NHL. Similar results were observed for all NHL subtypes analyzed. Clusters of NHL were spatially associated with benzene release sites located in metropolitan areas, but not with release sites in other areas of the state. CONCLUSIONS NHL incidence was significantly higher in census tracts that were closer, on average, to benzene release sites. Additional studies are needed to examine spatial patterns of NHL incidence in other geographic regions and interactions between benzene and other exposures. Cancer 2013;119:3309–17. © 2013 American Cancer Society.